Numerical modelling of compound channel flow - Filonovich, M. S.; Leal, J. B.; Rojas-Solorzano, L. (Nazarbayev University, 2014)
Most natural rivers have compound cross-section. Compound channel flow is characterized by complicated three-dimensional flow structures. These structures are called secondary flows and have been classified into two categories by Prandtl (1952). He distinguished the secondary flows of the first kind and of the second kind. The secondary flows of the the second type are typically about 2-3% of the maximum streamwise velocity (Nezu and Rodi, 1985), however, they have a major impact on the mean flow and turbulence structures.
Keywords: numerical modelling; channel flow; structures; anisotropic models